Development of Interactive Media Based on Adobe Animate Creative Cloud to Improve Student Learning Outcomes - Putri Roka Ismail; Hidayat Hidayat; Yusnadi Yusnadi (RIRAI Publisher, 2023)
The objectives of the research were (1) to produce interactive learning media based on Adobe Animate Creative Cloud for Social Studies class IV at Amaliyah Sunggal Private Elementary School, the sub-theme of the beauty of the cultural diversity of my country which was developed to be suitable for use as learning media, (2) to produce the use of Adobe-based interactive learning media. Animate creative cloud on social studies subjects in class IV Amaliyah Sunggal Private Elementary School on the sub-theme of the beauty of the diversity of my country which was developed effectively to improve learning outcomes. The research method uses research and development. Subjects were material expert validators, media experts, instructional media design experts, linguists, teachers and twenty five students. Product development is evaluated using a questionnaire. The results of the evaluation of the test subjects were analyzed descriptively qualitatively. The development model used in this study is the Thiagarajan model, known as the Four-D (4-D Model). The results showed that social studies interactive learning media based on Adobe Animate Creative Cloud in class IV Amaliyah Sunggal Private Elementary School was appropriate and effective for improving student learning outcomes in learning the theme of the beauty of the diversity of my country.